The Safe Recipient of SSC Transplantation Prepared by Heat Shock With Busulfan Treatment in Mice - Ma, Wenzhi (Cell Transplant, 2018)
Safety is the chief consideration in recipient preparation of spermatogonial stem cell (SSC) transplantation in mammals, especially humans. In this study, we compared the safety of the SSC transplantation recipients that were prepared both by testes heat shock plus testes busulfan injection (heat shock+busulfan(t)) and by busulfan intraperitoneal injection (busulfan i.p.) only. Our results showed that heat shock+busulfan(t) treatment significantly (p < 0.05) reduced mortality in mice and did not produce bone marrow cell toxicity. Furthermore, heat shock+busulfan(t) treatment directly damaged SSCs and exhausted almost all of the germ cells in the testis; the exhaustion of these cells is considered a key factor in the successful preparation of the recipients. Therefore, we used heat shock+busulfan(t) treatment to prepare recipients of SSC transplantation. Two months after SSC transplantation, the number and length of donor SSC-derived colonies in the testis of recipient in heat shock+busulfan(t) group was closed to that in busulfan i.p. group. Therefore, compared with busulfan i.p. treatment, heat shock+busulfan(t) treatment improved the safety of recipient preparation without reducing the efficiency of SSC transplantation. Two GFP-positive offspring were produced from 1 of the 20 recipients that had mated with female mice 72 days after SSC transplantation. In conclusion, heat shock with busulfan treatment is a safe method to prepare the recipient of SSC transplantation in mice.